Stereological study of the cells of dorsal root ganglia in male diabetic rats - NOORAFSHAN, A.; EBRAHIMPOOR, M. R.; SADEGHI, Y. (APMIS : acta pathologica, microbiologica et immunologica Scandinavica, 2001)
Most research on diabetes mellitus has focused on physiological and biochemical aspects of the peripheral nervous system, whilst little work has been done on morphological changes of the neurons. In the present study the effects of diabetes mellitus on cervical and lumbar dorsal root ganglia (C7 and L5) were investigated using modern stereological methods. Twelve adult male Sprague‐Dawley rats were randomly divided into two groups. Each group contained six male rats. Diabetes was induced in the experimental group by intraperitoneal injection of 50 mg/kg streptozotocin. At the end of 6 weeks, the rats were fixed by whole body perfusion transcardially with a buffered formalin solution. The seventh cervical and fifth lumbar dorsal root ganglia were removed and immersed in buffered formalin. After tissue processing, the ganglia were embedded in cylindrical paraffin blocks. Isotropic uniform random sections were obtained using the orientator method. Sections (5 μm thick) were selected and stained with Heidenhain's azan. Volume of perikarya of A‐ and B‐cells and their nuclei was estimated using the nucleator method. Before estimating the mean volume, the cells were sampled using the physical disector and point sampling method. Measurements showed that mean perikaryal and nuclear volume of A‐ and B‐cells of dorsal root ganglia (C7 and L5) was reduced in diabetic rats (p<0.05). B‐cell mean perikaryal volume in diabetic rats and A‐ and B‐cell mean nuclear volume were reduced by 66% on average. The mean volume of A‐cell perikarya was affected less than the others (average 33%). In addition, the difference between the perikaryal and nuclear volume of the seventh cervical and fifth lumbar dorsal root ganglia was not statistically significant. The present study, using stereological techniques, demonstrates reduced perikaryal and nuclear volume of the seventh cervical and fifth lumbar dorsal root ganglia in diabetic rats.